MORPHOLOGICAL STATE OF THE RENAL MEDULLA IN RATS IN CASE OF AN EXPERIMENTAL BURN INJURY UNDER CONDITIONS OF GEKOTON - Malikov, O.V. (World of Medicine and Biology, 2018)
The article presents structural changes of the renal medulla in experimental traumatic skin injury in rats under conditions of intravenous infusion of a colloid-hyperosmolar solution of gekoton. It was found that gekoton acts on the structure of the body as a cytoprotector. The cytoprotective effect is caused by induction of hypertrophy and hyperplasia of mitochondria. It also acts as a stimulator of mitophagia and an inhibitor of mitochondrial transduction of apoptotic signal. The obtained results are a kind of control and necessary for interpretation in comparison with the data to be obtained in the study of changes in the structural components of the renal medulla under conditions of infusion of other combined hyperosmolar solutions.
Keywords: burn; renal medulla; light and electron microscopy